Vertical and Horizontal Variability of Chlorophyll-a and Its Relationship with Environmental Parameters in the Waters of Sangihe and Talaud Islands, North Sulawesi, Indonesia - Firdaus, Mochamad Ramdhan; Rachman, Arief; Fitriya, Nurul; Wijayanti, Lady Ayu Sri; Rozirwan, Rozirwan; Purwandana, Adi; Prayitno, Hanif Budi; Alfiansyah, Yustian Rovi; Sianturi, Oksto Ridho; Sugeha, Hagi Yulia (Marine Science Department Diponegoro University, 2024)
The chlorophyll-a is an important biological parameter that could act as a proxy to indicate the abundance of phytoplankton and the primary productivity of an aquatic ecosystem. This paper investigates the vertical and horizontal variability of chlorophyll-a in the waters of Sangihe and Talaud Islands, Indonesia, and its correlation with water environmental parameters. In this study, the distribution of chlorophyll-a, temperature, salinity, and nutrients (NO3 and PO4) from the surface to a depth of 200 m (photic zone) was measured at 29 research stations. The results showed that the distribution of chlorophyll-a in the waters of the Sangihe-Talaud Islands was varied vertically and horizontally. The waters around the Sangihe Islands generally exhibited a higher chlorophyll-a distribution and shallower Deep Chlorophyll Maxima compared to the water around the Talaud Islands. The concentration of chlorophyll-a varied between 0.0017 and 1.2155 mg.m-3, with most of the water column in Sangihe-Talaud considered oligotrophic, although some stations or depths were mesotrophic or slightly eutrophic. The maximum chlorophyll-a concentration was found in the sub-surface layer at depths between 46 and 101 m. The low N:P ratio (<16) and N:Si ratio (<1) indicate that the water columns of Sangihe-Talaud, up to a depth of 200m, were N-limited. Based on the GAM analysis, chlorophyll-a concentration in Sangihe-Talaud waters was primarily regulated by temperature, salinity, and the N:P ratio, with weak influence from phosphate and the N:Si ratio. The analysis also suggests that primary productivity in Sangihe-Talaud is sensitive to temperature changes, indicating its vulnerability to future warming events.